Leadership of Private School Head Teachers for 21st Century: A Narrative Inquiry - Pandey, Kapil Jung; Tiwari, Sunita; Thapa, Jashu (Journal of Tikapur Multiple Campus, 2024)
The twenty-first century has brought many challenges in the education sector along with entire other sectors. The issue of accelerating globalization and digitalization has influenced the educational sector a lot. The stakeholders have faced many challenges in implementing the issue in their organization. The particular study has focused on the perceptions and role of school leadership in 21st-century schools. The study has tried to explore school leaders’ views. The particular research is based on the narratives of the school leaders based on their experiences, feelings, and expectations. Three school principals from private schools in Kathmandu were purposively chosen based on their execution of new practices in the school. They were interviewed physically and virtually and a conclusion was drawn from the process of coding, categorizing, thematizing, and meaning-making process. The school leaders have focused on organizational leadership, teamwork, and increased use of ICT as the major concern of schools and their leaders and they are found ready for every unpredictable situation that the school will be facing very soon in the complex, globalized, and culturally blended world making the educational organization service oriented. Still, there is room for development despite the great effort of head teachers.